Primary Disease Prevention for Southwest American Indian Families During the COVID-19 Pandemic: Camp in a Box - Gachupin, Francine C.; Caston, Elissa; Chavez, Christine; Bernal, Jacob; Cager, Phoebe; Harris, Drew; John, Tara; Remitera, Joe; Garcia, Charlotte A.; Romero, Victoria M.; Gchachu, Karina E.; Gchachu, Celeste R.; et al. (Frontiers in Sociology, 2021)
The goal of the American Indian Youth Wellness Camp in a Box was to engage, educate and empower families to improve their health and overall well-being during the COVID-19 pandemic. Camp in a Box was a 9-week program, inclusive of a 1-week intensive camp component followed by an 8-week booster component with content focused on nutrition, mental health and physical activity education. The Camp in a Box is a Tribal/Urban Indian-University partnership, and materials were developed to replace an existing weeklong residential camp and to comply with social distancing guidelines. Fourteen American Indian families from Tribal/Urban Indian communities in the southwestern United States participated (36 children aged 2–18 years; 32 adults). The intensive camp week included daily materials for families to complete together, Monday through Friday. Materials were provided for approximately 4 h of activities per day. The booster sessions began after camp week and included approximately 4 h of supplementary activities designed to be completed at any time most convenient for the family over the course of the week. Activities were designed to encourage interaction among family members with materials and supplies for parents and youth to participate. Self-reported outcomes suggested that families changed their eating habits to include more vegetables, less sweets and junk food. Parents reported an increase in family physical activity and that the activities brought the family closer together. Our Camp in a Box program was feasible and well-received until school began. During camp week, 100% of recruited families participated; at Booster Week 8, ten families (71%) remained enrolled and active. Camp in a Box is a feasible alternative to residential camps for promotion of health behaviors associated with metabolic disease prevention among American Indian families. In contrast to residential camps for youth, Camp in a Box offers an opportunity to engage the entire family in health promotion activities.